Criminal Liability of Postal Services in Transito Narcotics - Mahendra, Januar Rahadian; Nurviani, Novi (Faculty of Law, Universitas Slamet Riyadi, 2024)
This study analyzes the problems in the golden triangle of narcotics and criminal liability of sea freight forwarding services in transito narcotics crimes. The purpose of this research is to find out how the problems in the golden triangle of narcotics and criminal liability of sea freight forwarding services in transito narcotics crime. Based on the results of research and discussion, it can be seen that the golden triangle of narcotics has complex problems and requires assistance from other countries to overcome narcotics problems in their own countries. Through research and discussion, it is also known that there is no regulation on the transportation of narcotics by sea but it is different from the transportation of narcotics using the post. When using the post, the delivery service can be held criminally liable if it knows that the goods sent are narcotics, but if the delivery service does not know that the goods sent are narcotics then it cannot be held criminally liable. Although the delivery service cannot be held criminally liable if it does not know that the goods sent are narcotics, it can still be held legally liable, namely as a witness.